2008
DOI: 10.1002/ijc.23351
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin silencing reverses stabilization of mitochondrial integrity and chemoresistance in ovarian cancer cells by increasing their sensitivity to apoptosis

Abstract: Current approaches to the treatment of ovarian cancer are limited because of the development of resistance to chemotherapy. Prohibitin (Phb1) is a possible candidate protein that contributes to development of drug resistance, which could be targeted in neoplastic cells. Phb1 is a highly conserved protein that is associated with a block in the G0/G1 phase of the cell cycle and also with cell survival. Our study was designed to determine the role of Phb1 in regulating cellular growth and apoptosis in ovarian can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 38 publications
5
66
1
Order By: Relevance
“…30 In addition, PHB1 inhibits staurosporine-induced apoptosis and promotes survival in ovarian cancer cells. 31 Consistent with previous findings, our study shows that PHB1 inhibits H 2 O 2 -induced apoptosis in cardiomyocytes. Thus, (h and i) MiR-361 transgenic mice exhibit increased mitochondrial fission, apoptosis and myocardial infarction sizes in response to ischemia injury.…”
Section: Phb1supporting
confidence: 93%
“…30 In addition, PHB1 inhibits staurosporine-induced apoptosis and promotes survival in ovarian cancer cells. 31 Consistent with previous findings, our study shows that PHB1 inhibits H 2 O 2 -induced apoptosis in cardiomyocytes. Thus, (h and i) MiR-361 transgenic mice exhibit increased mitochondrial fission, apoptosis and myocardial infarction sizes in response to ischemia injury.…”
Section: Phb1supporting
confidence: 93%
“…In contrast to those in normal ovarian epithelium, a higher prohibitin expression level was observed in ovarian papillary serous and endometrioid carcinomas, which was inversely associated with cellular Ki-67 expression, a marker of cell proliferation and positively correlated with the cell survival marker X-linked inhibitor of apoptosis protein (XIAP). Prohibitin may be a negative regulator of cell growth and function as an antiapoptotic factor in ovarian cancer cells, as well as play an important role in determining the chemosensitivity of ovarian cancer cells [25]. In this study, we showed that prohibitin was specifically up-regulated by LH in ovarian epithelial cells by a proteomic method.…”
Section: Discussionmentioning
confidence: 63%
“…PHB1 has been shown to have a role in the regulation of apoptosis (11,13). We therefore examined whether transient knockdown of PHB1 results in the activation of the apoptotic pathway after treatment with paclitaxel.…”
Section: Transient Silencing Of Gstπ and Phb1 Partially Rescues Paclimentioning
confidence: 99%
“…It resides at the inner mitochondrial membrane where it serves as a protein chaperone (9,10). Recently, studies have shown that PHB1 has a role in the regulation of the apoptotic pathway (11)(12)(13). Additionally prohibitins have been found to reside on the cell surface of certain cells, including adipose endothelial cells (14,15).…”
mentioning
confidence: 99%